Study on the interlayer debonding and its effects on the mechanical properties of CRTS II slab track based on viscoelastic theory. (10th November 2019) - Zhang, Yanrong; Wu, Kai; Gao, Liang; Yan, Shang; Cai, Xiaopei
Highlights: A novel viscoelastic finite element model of CRTS II slab track was established. The effects of viscoelastic parameters during modelling were discussed. Critical conditions of interlayer debonding under temperature and vehicle loads were proposed. Specific influences of debonding size and locations on mechanical properties were estimated. Abstract: In this study, a novel viscoelastic finite element model of China Railway Track System (CRTS) II slab track incorporating viscoelastic parameters and a cohesive zone was established. Based on this model, the interlayer debonding between the prefabricated concrete slabs and the cement asphalt mortar layer and its effects on the mechanical performance of track structure were systematically investigated. Firstly, the validity of the viscoelastic model was verified by comparing the simulated results with experimental data. Then, the initiation mechanism of debonding under temperature gradient loading and under coupling actions of temperature and dynamic vehicle loadings was analyzed and then compared with that based on a common elastic model. Finally, typical interlayer debonding cases with different locations and sizes were purposely set up and their effects on the vertical stresses and vertical displacements of the track were discussed. Results show that after introducing viscoelastic parameters, the maximum opening height and the extension width of debonding increase rapidly, while the temperature gradients of initiating debonding keep unchanged but the penetration temperature gradients significantly decrease. On the other hand, the vertical stresses and vertical displacements of track structure are hardly affected by the debonding in the middle, slightly changed by the debonding length at the edge and significantly affected by the debonding width at the edge. With the increase of debonding area, the vertical stresses and vertical displacements significantly increase, especially when the debonding area is larger than critical values. Compared to the elastic model, the use of the viscoelastic model leads to larger vertical stresses and displacements. It is believed that the incorporation of viscoelastic parameters effectively enhances the performance of FEM, which can better predict the initiation of interlayer debonding and the dynamic response of track structure.